REGIONAL FINANCIAL MANAGEMENT AND ACCOUNTABILITY (Implementation of Article 4 of Government Regulation Number 105 Year 2000 on House Rehab Program to Wealthy Society in Batu City) - Yoni Kiswandono (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Social welfare is the fulfillment of the conditions of material, spiritual, and social citizens to live a decent and able to develop themselves, so that it can carry out its social function. Batu City has to take care of household affairs and financial areas, including the problem of social poverty. Based on the content of Article 4 Government Regulations No. 105 Yeat 2000 on Regional Financial Management and Accountability, the Batu City government must manage local financial public interest, including for social welfare in batu City. BPMPKB and Department of Social and Labor become research location. BPMPKB has a program called Tridaya, namely in the fields of infrastructure, training, and economic. Department of Social and Labor also has programs aimed to maximized the social welfare of Batu City by utilizing the natural potential.Key word : Social welfare, regional financial management and accountability.